DNA-PK Phosphorylation of RPA32 Ser4/Ser8 Regulates Replication Stress Checkpoint Activation, Fork Restart, Homologous Recombination and Mitotic Catastrophe - Ashley, Amanda K. (2014)
Genotoxins and other factors cause replication stress that activate the DNA damage response (DDR), comprising checkpoint and repair systems. The DDR suppresses cancer by promoting genome stability, and it regulates tumor resistance to chemo- and radiotherapy. Three members of the phosphatidylinositol 3-kinase-related kinase (PIKK) family, ATM, ATR, and DNA-PK, are important DDR proteins. A key PIKK target is replication protein A (RPA), which binds single-stranded DNA and functions in DNA replication, DNA repair, and checkpoint signaling. An early response to replication stress is ATR activation, which occurs when RPA accumulates on ssDNA. Activated ATR phosphorylates many targets, including the RPA32 subunit of RPA, leading to Chk1 activation and replication arrest. DNA-PK also phosphorylates RPA32 in response to replication stress, and we demonstrate that cells with DNA-PK defects, or lacking RPA32 Ser4/Ser8 targeted by DNA-PK, confer similar phenotypes, including defective replication checkpoint arrest, hyper-recombination, premature replication fork restart, failure to block late origin firing, and increased mitotic catastrophe. We present evidence that hyper-recombination in these mutants is ATM-dependent, but the other defects are ATM-independent. These results indicate that DNA-PK and ATR signaling through RPA32 plays a critical role in promoting genome stability and cell survival in response to replication stress.